A Historical Study of the Effects of the 1930 Earthquake on the Human Geography and History of Selmas City and its Surrounding Region - Zeinab Ahmadvand; Tohid Malekzadeh Dilmaghani (برنامه ریزی فضایی)
Abstract:Problem Statement: Selmas City situated in West Azerbaijan province at coordinates 38° 12ʹ north and 44° 46ʹ and 40ʺ east experienced a significant earthquake almost a century ago. On Tuesday night or Wednesday morning, May 17, 1930, the city was struck by a powerful earthquake measuring M=7.4 on the Richter scale and 2.7 on the Geophysics Institute scale. This earthquake stood as one of the most devastating seismic events in the history of Azerbaijan and the broader Middle East region up until that time. The year 1930 became synonymous with seismic activity, earning the name "Selmas" in the annals of seismology. Objective: This research aimed to investigate and examine the impact of the May 1309 earthquake on the human geography, as well as the historical and ancient structures of Selmas City and its surrounding region. Methodology: This study adopted a fundamental research approach, employing a descriptive and analytical methodology. It relied on primary sources, such as documents, libraries, and field studies encompassing geology and earthquakes. Results: The findings of this research revealed that the Selmas earthquake had led to the destruction of Dilmaqan City and approximately 60 villages within Selmas Plain and its vicinity. The extent of the damage extended from Selmas Plain to Qatur, Khoy, and Upper Zab Regions in Turkey. Alongside the loss of 2,500 to 4,000 lives, this earthquake had caused substantial damage to numerous historical and ancient structures throughout the entire Selmas Region.Keywords: Selmas, Azerbaijan, Historical Building, Earthquake. Introduction:Nearly a century ago, on May 16, 1930, the city of Selmas experienced an earthquake measuring M=5.5 at 10:00 in the morning. This initial earthquake resulted in the destruction of several villages and caused damage to the roofs and walls of rural houses. However, the most significant event occurred later that night, marking the main earthquake. At midnight on Tuesday or the morning of Wednesday, May 17, 1930, a powerful earthquake measuring M=7.4 struck Selmas, leading to the catastrophic destruction of the city and the majority of its surrounding villages. This earthquake stood as one of the most devastating seismic events in the Azerbaijan region, resulting in the complete devastation of Dilmaqan City and approximately 60 villages within Selmas Plain and its periphery. The human casualties of this earthquake ranged between 2,500 and 4,000 lives lost. The impact was not limited to human life as numerous ancient and historical structures in Selmas fell victim to the disaster. The 4-meter wall of Dilmaqan City, mosques, Christian churches, the medieval minarets of Mirkhatun in the old city, and many old bridges were among the structures destroyed. The earthquake caused significant changes in the natural, human, and historical geography of Selmas Region. Materials & Methods:The methodology employed in this study was based on both descriptive and analytical methods, drawing upon primary sources, such as historical and geographical texts, official reports, accounts from local residents, and field studies encompassing geology and earthquakes. Research Findings:The findings presented in this research were derived from a comprehensive review of historical literature and localized investigations. The significant and devastating earthquake that struck Selmas in the year 1309 stood out as one of the most destructive seismic events in Azerbaijan Region. Occurring 15 hours after the initial pre-earthquake tremor, the main earthquake took place at midnight on Tuesday or the morning of Wednesday, May 17. Its impact resulted in the complete destruction of Dilmaqan City and approximately 60 surrounding villages within Selmas Plain and the adjacent areas. The extent of devastation extended from Selmas Plain to the village of Qatur and the Upper Zab Road in Turkey, leading to the tragic loss of 2,500 to 4,000 lives in Selmas. This article delved into the examination of the morphological changes and transformations caused by Selmas Earthquake, as well as the extent of damage inflicted upon ancient monuments in Selmas Region. Discussion of Results & Conclusion:The period following the Safavid era was marked by instability, resulting in a scarcity of significant archaeological monuments in Selmas Area. If any structures existed, they were likely constructed during the Qajar era, but unfortunately, they were largely destroyed in the aftermath of the First World War. Analysis of the ancient remnants in Selmas indicated that the structures situated in mountainous regions, such as ancient castles and Urartoi crypts, or those constructed using stone exhibited relatively good resistance against the powerful Selmas earthquake with a magnitude of 7.2. However, all the structures made of clay and other similar materials vanished.The Selmas earthquake of such magnitude brought about significant changes to the tectonic, seismotectonic, and geomorphological aspects of Selmas Region and the enduring impact of these changes is evident to this day. Notable transformations included the destruction of urban infrastructure, damage to residential areas, formation of earthquake faults and land fissures, hill collapses, landslides within the region, fluctuations in the water level of Lake Urmia accompanied by violent waves, alterations in the water level of wells, and emergence of water springs (Bolaghi Earthquake).Approximately two weeks after the city's devastation, a new city was established one kilometer away from the ruins of the earthquake-stricken city in the present location of Selmas. This new city was meticulously designed with proper urban planning and engineering, following a grid pattern. Today, little remains of the ruins of the earthquake-stricken city as they have been repurposed for agricultural and residential use.